Moral Paradox And Legal Pragmatism: A Multi-Analysis Of The Cooperating Accomplice (Justice Collaborator) In Indonesia - Yudhi Hertanto; Ibrahim Fajri (Universitas Ibn Khaldun Bogor, 2026)
The institution of the cooperating accomplice, universally known as the Justice Collaborator (JC), represents a crucial legal breakthrough in combating extraordinary crimes such as corruption, money laundering, and organized crime in Indonesia. However, its implementation triggers intense doctrinal debates because it entails granting legal incentives to criminal perpetrators. This study aims to analyze the existence and effectiveness of the JC through an interdisciplinary approach that integrates dogmatic-juridical, socio-legal, and philosophical perspectives. Employing a normative-empirical (socio-legal) research method alongside statutory, conceptual, and contemporary case approaches, this article dissects the structural tensions inherent in law enforcement. Juridically, the study reveals that regulatory overlaps between SEMA No. 4 of 2011 and Law No. 31 of 2014 generate operational uncertainty regarding the criteria for identifying the